Are cellular mechanosensors potential therapeutic targets in osteoarthritis?. (April 2014) - Drexler, Stefan; Wann, Angus; Vincent, Tonia L
The role of mechanical factors in driving osteoarthritis is undisputed, but historically this was largely explained by chronic attrition of the articulating surfaces. The finding that mice deficient in matrix-degrading enzymes were protected from experimental osteoarthritis (OA) suggested an alternative explanation: that mechanosensitive pathways drive the enzymes responsible for cartilage breakdown. Mechanical factors are also important for joint homeostasis and are therefore both good and bad for the joint. Several mechanosensing pathways have been identified in a variety of cell types in vitro and in vivo . Here, we review those pathways with demonstrable roles in chondrocyte mechanotransduction including ion channels, integrins, the primary cilium and the pericellular and intracellular matrices. At least two of these pathways, involving release of FGF2 from the pericellular matrix and activation of TRPV4 are chondroprotective in OA models in vivo . We discuss the potential for modulating selective mechanosensing pathways for therapeutic benefit in OA.